Bank Acquisitiveness and Bailouts: Evidence on European Banks during the 2008 Financial Crisis - SAQIB AZIZ; JEANJACQUES LILTI; KHALID EL BADRAOUI (Bankers, Markets & Investors, 2017)
Theoretical prediction that banks may pursue M&A strategies to exploit too-big-tofail subsidies caught attention in the backdrop of 2008 financial crisis. Using a sample of 1603 M&A transactions of large European banks over the period of 1990-2006, we investigate whether and how bank acquisitiveness relate with their bailout support during the recent financial crisis. Our findings suggest towards a positive relation of bank acquisitiveness not only with the probability of external support but also with the level of such support. We also find that the bailout beneficiary banks in our sample demonstrated a significant restraint in their post-crisis acquisitiveness. While our findings broadly substantiate ex-post materialization of safety-net benefits for highly acquisitive banks, terming the post-crisis restraint on acquisitive behaviour of bailout beneficiaries as voluntary or the one imposed by regulators rests an open question.